Ruimte en identiteit in die werk van “Gekleurde" skrywers met spesiale verwysing na E. K. M. Dido - Lewis, Minnie Miriam (Afrikaans and Netherlandic Studies, 2014)
This study has set out to highlight and investigate the contributions, to the Afrikaans literature, by writers of ""Colour"", as marginalized writers, especially after 1990. It must be indicated that a special place in the thesis, chapter five, has been devoted to the female writer of ""Colour"", EKM Dido, and the invaluable contributions she has made to Afrikaans literature. This chapter deals exclusively with all Dido's novels to date, and includes detailed discussions and analysis of important issues and aspects in the said novels. The thesis has focused on various ""Coloured"" writers, both male and female, and their contributions. The fact that naming and terms denoted to and used for various racial groupings are such thorny in South African society, terminology used to refer to these writers of ""Colour"" in this thesis initially seemed to pose a problem, but motivating the use of certain terms, to highlight and not relegate to the margins, solved this problem I believe.